Laplacian Spectrum of Some Classes of Self Complementary Perfect Graphs (Journal of Informatics and Mathematical Sciences, 2013)
In this paper we study Laplacian spectrum of self-complementary (sc), sc comparability and sc chordal graphs. Some results on Laplacian cospectrality and Laplacian energy are obtained. We also propose two conjectures.
Keywords: L-Cospectral; Laplacian energy